Is it possible to influence adolescents sleep habits with education-based intervention? A pilot study - Freyja Hlín Valgeirsdóttir 1995- (2019)
Adolescents today are lacking sleep because of their busy daily schedule. Their sleep deprivation is affected by psychosocial, environmental and biological factors, which can lead to lack of performance at school and more difficult to stay awake during the day. The purpose of this pilot study was to see if education-based intervention could possible influence adolescents sleeping habits in a compulsory school in Iceland. Altogether, a sample of 21 students, 11 girls and 8 boys participated in an education-based intervention about their sleeping habits. Students also had to answer the Pittsburg Sleep Quality Index (PSQI) and a 20-item scale which perceived students background which is used as a baseline and a follow-up measure. The results showed that adolescents got their 8 hours of sleep as recommended. Adolescents that spend time on screen media are not likely to sleep less than recommended. There was also a negative effect on adolescents drinking caffeine and likely to sleep less than recommended. Lastly, education-based intervention enhanced students’ knowledge on sleep. In conclusion, there was only a significant difference on students’ knowledge about sleep but not on their sleeping habits. Keywords: adolescents, sleep quality, caffeine intake, screen media, biological factors, intervention-based education, Pittsburgh Sleep Quality Index Ungmenni í dag skortir svefn vegna þess hversu upptekin þau eru við daglegar skyldur. Lífræðilegir-, sálfélagslegir- og umhverfisþættir hafa áhrif á svefnskort sem getur leitt til slakari framstöðu í skóla og erfiðleika við að halda sér vakandi yfir daginn. Tilgangur þessarar rannsóknar var að kanna hvort íhlutun sem byggir á fræðslu hafi áhrif á bættar svefnvenjur ungmenna á grunnskólum á Íslandi. Úrtakið var samtals 21 nemandi, 11 stelpur og 8 strákar sem tóku þátt í íhlutun sem byggð var á fræðslu um þeirra svefnvenjur. Nemendur svöruðu einnig Pittsburg Sleep Quality skalanum (PSQI) og 20 bakgrunnspurningum sem notað var sem grunnlína fyrir rannsókn og eftirfylgni ...